2015
DOI: 10.1186/s12986-015-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-β by a novel PPAR-γ agonist, chrysin, salvages β-receptor stimulated myocardial injury in rats through MAPKs-dependent mechanism

Abstract: BackgroundPharmacological stimulation of peroxisome proliferator-activated receptor-gamma (PPAR-γ) has been recognized as a molecular switch in alleviating myocardial injury through modulating oxidative, inflammatory and apoptotic signaling pathways. This study was designed to elucidate the effect of chrysin, a novel PPAR-γ agonist and its functional interaction with TGF-β/MAPKs in isoproterenol-challenged myocardial injury in rats.MethodsMale Wistar Albino rats were either subjected to vehicle (1.5 mL/kg, p.o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Similar results were obtained when PPARγ agonist was used. These results demonstrate that PPARγ is a critical factor in inhibiting TIF, in agreement with previous studies showing the critical role of PPARγ in fibrosis [55, 56]. However, further studies are still needed to investigate whether TGF-β1-induced myofibroblast formation/transdifferentiation contributes to renal TIF in DN.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were obtained when PPARγ agonist was used. These results demonstrate that PPARγ is a critical factor in inhibiting TIF, in agreement with previous studies showing the critical role of PPARγ in fibrosis [55, 56]. However, further studies are still needed to investigate whether TGF-β1-induced myofibroblast formation/transdifferentiation contributes to renal TIF in DN.…”
Section: Discussionsupporting
confidence: 91%
“…Our data in this study showed that inactivation of MAPK inhibited viability and induced apoptosis of esophageal cancer cells by PPARγ agonist or siRNA targeting ERK, JNK, and p38, which are consistent with these results. PPARγ acted as a molecular switch in moderating myocardial injury via blocking the MAPK pathway in isoproterenol-induced myocardial injury in rats [43]. PPARγ agonist suppressed ERK MAPK signal activation to inhibit activity of cellular NO and reactive oxygen species formation, counteracting LPS-induced inflammatory response in pulp cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying SAP-induced ALI is currently unknown. Previous studies investigating MAPK signaling pathways have greatly enriched the current understanding of the molecular mechanisms underlying various biological stimuli, including inflammatory mediators ( 31 33 ). Wang et al ( 19 ) demonstrated that, in rat PMVECs treated with lipopolysaccharides, overexpression of Angptl4 or rosiglitazone treatment inhibited the Raf/[MAPK/extracellular signal-regulated kinase (ERK)]/MAPK cascade and was able to protect against increased permeability induced by F-actin depolymerization.…”
Section: Discussionmentioning
confidence: 99%